After integration: Islam, conviviality and contentious politics in Europe - Burchardt, Marian; Michalowski, Ines (Islam und Politik, 2015)
The integration of Muslims into European societies is often seen as a major challenge that is yet to be confronted. This book, by contrast, starts from the observation that on legal, political and organizational levels integration has already taken place. It showcases the variety of theoretical approaches that scholars have developed to conceptualize Muslim life in Europe, and provides detailed empirical analysis of ten European countries. Demonstrating how Muslim life unfolds between conviviality and contentious politics, the contributors describe demographic developments, analyze legal controversies, and explore the action of government and state, Muslim communities and other civil society actors. Driving forces behind the integration of Islam are discussed in detail and compared across countries. Content The book features theoretical perspectives on the legal, political, and social inclusion of Islam and case studies of Austria, Belgium, Denmark, France, Great Britain, the Netherlands, Portugal, Spain, Sweden and Switzerland. Target Groups Students and researchers in political science, sociology, migration studies, international relations and religious studies The Editors Dr. Marian Burchardt is a researcher at the Max Planck Institute for the Study of Religious and Ethnic Diversity in Göttingen. Dr. Ines Michalowski is a researcher at the WZB Berlin Social Science Center